Inclusive education in Chemistry and Environmental Education: the use of games for the deaf students inclusion (Research, Society and Development, 2022)
Chemistry is a fundamental science for society. Within the educational context, teaching approaches out of context with reality, such as the lack of relationship with Environmental Education (EE), make learning uninteresting for students. This problem intensifies for deaf students, due to the lack of teaching actions that include these students in the school environment. Therefore, this article aims to develop an Educational Ludic Game (ELG), supported by the concepts of Green Chemistry (GG) and the 6th (sixth) Sustainable Development Goal (SDG), for a high school class with hearing students and 1 (one) deaf student. The research was developed through a qualitative approach of participatory nature and, through it, it was verified the effectiveness of the implementation of Active Methodologies (AM) in Inclusive Education (IE). Through this, the use of games in the learning of deaf students stimulates participation and interaction within the classroom. Such pedagogical action demonstrated the importance of the cultural artifacts of the Deaf Community (DF), mainly, the work together with the Sign Language Interpreter Translators (SLIT). Thus, this work is expected to contribute to the transformation of a more accessible and inclusive education.